Leucemia linfóide aguda infantil no peculiar contexto amazônico. - CAJADO, Luciana Corrêa de Sena (2023)
The Acute Lymphoblastic Leukemia (ALL) is the most common cancer in the childhood, but the disease’s kind of evolution and the quality of the assistance which the pediatric patients receive are unknown in a lot of regions in the world – among them, the Amazon region, in Brazil. OBJECTIVE: To identify a local profile of pediatric patients diagnosed with ALL and assisted in a reference health service in the Amazon region; to describe the ALL in its clinical and laboratorial presentation and to analyze some clinical-epidemiological factors influences in three of the possible endings in this population: complete clinical remission, relapse and death. METHODS: Clinical-epidemiological study (observational, individual and analytic), with a retrospective design in series of cases, from 2003 to 2011. Patients with ALL were included according the following characteristics: to be from zero to twelve years old; and to be admitted from January/2003 to January/2008, in the Pediatric Sector of the Ofir Loyola Hospital (OLH). RESULTS: There were 152 patients in the study: 62.5% were boys and 37.5% girls. The age’s peak of incidence was with three years old and the average, 5.1 years old. Browns, Whites, Blacks, Indians and Yellows races/colors were found in this population: 71.1%, 11.2%, 3.9%, 0.7%, 0.7% and 12.5%, respectively. The origin was distributed among: Belem metropolitan region (27.6%), other towns in Para State (55.3%) and cities in other Brazilian States (16.4%). The spent time between the symptoms beginning and the admission at the OLH was 65.8 days (average). In the admission, 8.5% had central nervous system infiltration and 1% of the boys had testicle infiltration. Pancytopenia was the most found laboratorial standard, just as the blasts cells count over 85% in myelogram. There was more ALL cells B occurrence (36.2%) than other kinds, just as the subtype B common (30.2%). 98% of the treatments used chemotherapy protocols; only 0.7% of the patients was submitted to the bone marrow transplantation. The found endings were: death during the treatment (52%); complete clinical remission/cure (30.2%); treatment continuous to the first clinical remission (5.3%); treatment of relapse after the first finished treatment (4.6%); treatment of relapse without finishing the first treatment (3.9%); abandonment (3.3%); transference (0.7%). There was significant statistical association between: death and age, brown color, lack of pain in limbs in the admission, presentation of mucositis as co-morbidity on the diagnosis, no change of chemotherapy protocol during the treatment, no realization of intrathecal therapy, sepsis during the treatment, just as relapse and a long time of treatment; between relapse, male sex and late change of protocol; between cure and age, pale skin on the diagnosis and pain in limbs in the admission, realization of intrathecal therapy, no change of protocol, lack of relapse and having a treatment with a longer time. CONCLUSION: With significant statistical association mainly linked to the clinical presentation on the diagnosis and admission and to the conducts and complications during the treatment, it is responsibility of the health service reanalyze proposals of improvements to the assistance with the main objective of obtaining best results in the childhood cancer care in this Brazilian region.